2019
DOI: 10.1186/s12860-019-0185-4
|View full text |Cite
|
Sign up to set email alerts
|

Short telomeres correlate with a strong induction of cellular senescence in human dental follicle cells

Abstract: Background Dental follicle cells (DFCs) are dental stem cells and interesting options for regenerative therapies in dentistry. However, DFCs acquire replicative senescence in long-term cultures, but little is known about molecular processes. In previous studies, we observed that DFC cell lines become senescent at different rates. We hypothesized that short telomere length and increased DNA damage with genomic instability correlate with the accelerated induction of cellular senescence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…Previous studies on telomere length in dental pulp stem cells and induction of cellular senescence have shown similar results [33]. Interestingly, the telomeric erosion did not occur differently in the 2 cell lines during cell culture since almost no erosion was found for DFC_F and DFC_S in senescent DFCs [29]. Genomically higher rates of DNA damage and chromosome reorganization or aberration in DFC_F was the reason for the accelerated induction of cellular senescence.…”
Section: Telomere Length and The Induction Of Cellular Senescence In supporting
confidence: 65%
See 3 more Smart Citations
“…Previous studies on telomere length in dental pulp stem cells and induction of cellular senescence have shown similar results [33]. Interestingly, the telomeric erosion did not occur differently in the 2 cell lines during cell culture since almost no erosion was found for DFC_F and DFC_S in senescent DFCs [29]. Genomically higher rates of DNA damage and chromosome reorganization or aberration in DFC_F was the reason for the accelerated induction of cellular senescence.…”
Section: Telomere Length and The Induction Of Cellular Senescence In supporting
confidence: 65%
“…Telomeric lengths of 5 DFC cell lines were almost similar, but 1 cell line had shorter telomeres. This cell line (DFC_F) with short telomeres was compared with another cell line with longer "standard" telomeres (DFC_S) [29]. Although we expect cells with shorter telomeres to have higher β-galactosidase activity than cells with longer telomeres, the opposite was observed in this study.…”
Section: Telomere Length and The Induction Of Cellular Senescence In contrasting
confidence: 60%
See 2 more Smart Citations
“…A previous study suggested that DFCs exhibited features of cellular senescence after being expanded after more than 14 cell passages, displaying decreased cell proliferation, enlarged cell size, and upregulated expression of β -galactosidase [137]. Short telomeres and increased DNA damage with genomic instability were correlated with the accelerated induction of cellular senescence [138]. Moreover, the osteogenic differentiation of DFCs was inhibited due to cellular senescence, followed with a lower extent to differentiate into biomineralizing cells [137].…”
Section: Senescence and Apoptosis Characteristics Of Dfcsmentioning
confidence: 99%